The High Prevalence of Functional Complement Defects Induced by Chemotherapy - Keizer, Mischa P.; Kamp, Angela M.; Aarts, Cathelijn; Geisler, Judy; Caron, Huib N.; van de Wetering, Marianne D.; Wouters, Diana; Kuijpers, Taco W. (Frontiers in Immunology, 2016)
Introduction: To date, oncology patients are more dependent on non-cellular host defense against pathogens due to intensive (chemo)therapy-related bone marrow suppression. Since data on complement functionality in oncology patients are limited, we aimed to investigate the innate complement function in relation to the type of malignancy and therapy in a longitudinal cohort of patients. Methods: A large single-center, prospective non-intervention study was conducted, in which blood samples were taken from patients before, during and after treatment with chemotherapy and/or subsequent admittance for (febrile) neutropenia. Results/findings: Analysis of 48 patients showed a high percentage of defects in complement activity of the alternative pathway (19.1%), the classical pathway (4.3%) or both (42.6%). Post-hoc analysis of six different treatment protocols with more than 3 patients each showed distinct effects of specific therapies. Whereas patients treated according to the Ewing, EpSSG-rhabdomyosarcoma or SIOP CNS germ cell tumor protocol showed no defects, patients treated according to the ALL-11 (leukemia), the EURAMOS I (osteosarcoma) or the ACNS (medulloblastoma) protocols showed an almost universal reduction in complement function. Although we could not explain the reduced complement functionality under all conditions, a strong effect was observed following high-dose methotrexate or ifosfamide. Conclusion: Acquired complement defects were commonly observed in more than 50% of oncology patients, some of which associated with certain chemotherapeutic drugs. Additional studies are needed to determine the clinical and therapeutic context of complement defects and their possible effect on treatment outcome or the increased risk of infection.